American Beauty: The art of work in the age of therapeutic masturbation. Issue 1 (1st March 2015) - Weeks, Mark
American Beauty (Mendes, 1999) was an outstanding commercial and critical success at the turn of the millennium, generating considerable media and eventually scholarly attention. In the various critical approaches to the film, some attention has been given to its portrayal of erotic fantasy, yet a related element that has not been dealt with, though occasionally noted, is its conspicuous depictions of, and references to, physical autoeroticism. Observing a certain uneasiness towards discussions of the subject, this article argues that the foregrounding of masturbation, far from being incidental prurience, reflected and consolidated a significant cultural movement. While in part it was an outgrowth of a liberalization of discourses around sex, a closer examination of American Beauty in its cultural–historical context reveals its connection to important neo-liberal changes in the concept of the individual self and its relationship to society. Indeed, it is associated within the film itself to changes in labour economic and familial relations around that time which inform the United States today. Neither denouncing nor promoting the portrayal of masturbation, the article ultimately seeks to demonstrate the utility and significance of bringing the discussion of embodied forms of autoerotic pleasure more thoroughly into cultural analysis.